POLA ASUH ORANG TUA TERHADAP KESEHATAN MENTAL ANAK SELAMA PEMBELAJARAN DARING DI JALAN CAGAR ALAM - Ishmah Alya Diska; Nurul Hidayati (TATHWIR: Jurnal Pengembangan Masyarakat Islam, 2021)
Online learning has led to changes in parenting by parents for their children on Cagar Alam street, Depok City. The pandemic causes children to become stressed because they study from home and lack socialization with others. The research uses qualitative methods. Data collected by interview and direct observation techniques. Things that have changed in parenting are first, when the COVID-19 pandemic, parenting by parents more heavier than before a pandemic, because parents have to control their children's learning activities while at home. When studying at school, children may be more supervised by their teachers, but when studying at home, parents must supervise and control their children's learning activities. Second, parenting style in controlling children in playing gadgets. During the COVID-19 pandemic, parents must control their children more when playing gadgets. Due to online learning, children become addicted to playing gadgets which make their mental health disturbed and they become lazy to study. And third, children feel stressed and bored constantly at home which results in the child's mental health being disturbed. It is parents who have an important role in raising their children so that they are not stressed.